Modelo de referência para gestão de projetos de museus e exposições - Ana Cecilia Nascimento Rocha (2012)
The main purpose of this doctoral dissertation, titled Reference Model for Project Management in Museums and Exhibits, is to prepare a homonymous term of reference to serve as guideline for the management of projects, with emphasis on architecture and expography. The theoretical framework was the PMBOK (Project Management Body of Knowledge), in addition to the chief methodologies and bibliographical references in the field of Project Management of our days. Its structure covers the Project managers whole preparation: theoretical and historical background in museology, critical analysis of the new museological concepts museographic effects, preventive conservation in museums and exhibits. Among the chief contributions of this work, we must highlight: the adaptation of the current methodologies, with the addition of our personal contributions, producing a specific reference model for the case of museums and exhibits, saving the Project managers time and increasing the final products quality; the structuring, in the form of slip cards, of acclaimed text methodologies, in addition to our personal contributions, working toward an optimized route of diagnosis for museums; the inclusion and practical connection between the project teams processes and routines and the institutions master plan, considering the mission and the corporate environment in which that institution is inserted; the consolidation of a process of creative and software-dependent projects, totally focused on simultaneous engineering and cooperation between professionals, understanding that such technologies are the future, and, for many, the present of the project activity; finally, the synthesis of the body of knowledge essential to the museums manager, from the conceptual and historical-theoretical analysis of museology to issues of preventive conservation, serving as a starting point to the journey toward the training of professionals who work in our museums and exhibits.